2017
DOI: 10.5539/jas.v10n1p139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Additives on Rabbit Performance, Carcass Traits and Some Blood Constituents under Egyptation Summer Season

Abstract: Sixty 7-week-old New Zealand White rabbits were randomly distributed into 5 equal experimental groups. The experimental rabbits were fed the tested diets till 14 weeks of age during summer season. The basal diet without feed additives (control; T1) and the other experimental diets were supplemented with enzymes at 0.5 g/kg (T2), organic acids at 1.0 g/kg (T3), β-pro at 0.2 g/kg (T4) or their combination (T5). The criteria of response were body weight, weight gain, feed consumption, feed conversion ratio, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
(47 reference statements)
3
8
1
Order By: Relevance
“…The current finding is in harmony also with the result of Bhatt et al (2017), who found that rabbits given probiotic(Lactobacillus acidophilus)-enriched drinking water displayed significantly better daily weight gain compared with the control group. The positive effects of supplemental probiotics on growth rate of rabbits have also been reported by El-Deek et al (2013), Amber et al (2014), Chandra et al (2014), Lam Phuoc and Jamikorn (2017) and Sherif (2018). On the contrary, other authors found no positive effect of probiotics on growth performance of rabbits (Matusevicius et al, 2006;Kimse et al, 2008;Rabie et al, 2011;Fathi et al, 2017).…”
Section: Effect Of Dietary β-Pro Supplementationsupporting
confidence: 61%
See 1 more Smart Citation
“…The current finding is in harmony also with the result of Bhatt et al (2017), who found that rabbits given probiotic(Lactobacillus acidophilus)-enriched drinking water displayed significantly better daily weight gain compared with the control group. The positive effects of supplemental probiotics on growth rate of rabbits have also been reported by El-Deek et al (2013), Amber et al (2014), Chandra et al (2014), Lam Phuoc and Jamikorn (2017) and Sherif (2018). On the contrary, other authors found no positive effect of probiotics on growth performance of rabbits (Matusevicius et al, 2006;Kimse et al, 2008;Rabie et al, 2011;Fathi et al, 2017).…”
Section: Effect Of Dietary β-Pro Supplementationsupporting
confidence: 61%
“…Under such stressful situations, the supplementation with probiotics for rabbits would be beneficial to encourage the growth and proliferation of certain strains of beneficial bacteria in the gastrointestinal tract at the expense of less desirable ones (Sharma et al, 2016). Probiotic supplementation has been found to improve the growth rate and the efficiency of feed utilization in rabbits (Amber et al, 2014;Ren et al, 2016;Bhatt et al;2017;Lam Phuoc and Jamikorn, 2017;Sherif, 2018). Other studies, however, showed no positive effects of probiotics on growth performance of rabbits (Ewuola et al, 2011;Shrivastava et al, 2012;Fathi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Matusevicius et al (2006) compared with control group of rabbits, the weight gain of NZW rabbits fed 400 mg/kg of probiotic Bio Plus 2B ® was not significantly different. Recently, Sherif (2018) found that rabbits reared under stress summer conditions receiving enzymes at 0.5 g/kg, β-pro ® at 0.2 g/kg, organic acids at 1.0 g/kg or their mixture of enzymes, βpro ® and organic acids in the diet had the positive effects on daily weight gain compared with control group.…”
Section: Growth Performancementioning
confidence: 99%
“…The better rate of growth, FCR and rate of mortality with oral administration of ZAD ® may be because of including probiotics that can improve the intestinal balance of the host animal, impact of caecal fermentation and the bowel weight in rabbits (Kermauner and Struklec, 1999); improved the status of health and intestinal function of growing rabbits (Trocino et al, 2005 andKritas et al, 2008). In the other wise, dietary β-pro ® (probiotics+ enzymes) or a mixture of organic acids, βpro and enzymes can be improving the rabbit performance (Sherif, 2018).…”
Section: Growth Performancementioning
confidence: 99%
“…High stocking densities have an adverse effect on the performance of rabbits. Cage density and housing system can also affect welfare and production of rabbits (Szendro andLuzi, 2006 &Sherif 2018). Growth performance of rabbits depends on group size and cage dimensions.…”
Section: Introductionmentioning
confidence: 99%